Analisis Faktor-Faktor yang Mempengaruhi Penggunaan Sistem Informasi Pada Kinerja Karyawan BPR Lestari di Denpasar - Trijayanti, Ni Komang; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p10, 2018)
Companies in implementing information systems technology must pay attention to the extent to which the success of the system has a positive impact on improving the performance of individuals and organizations. The purpose of this study is to analyze the factors that influence the use of information systems on employee performance. This research was conducted at PT BPR Sri Artha Lestari in Denpasar with 45 employees as respondents . Data analysis technique used is multiple linear regression analysis. Based on the analysis result found that social influence and perceived ease of use have positive effect on perceived usefulness. Computer self efficacy and facilitation conditions positively affect perceived ease of use. Social influence, perceived usefulness, and perceived ease of use have a positive effect on attitudes toward the use of information systems. Perceived usefulness has a positive effect on employee performance, attitudes toward the use of information systems have no effect on employee performance. Keywords: information systems, use of information systems, employee performanc e